The colonies of law : - Shamir, Ronen (Cambridge University Press, 2000)
Treating law as an essential cultural component in a nation-building project, this book offers a socio-historical analysis of a community-based system of justice under colonial rule. It traces the attempts of Jewish jurists-nationalists to establish a non-religious system of Hebrew Courts in British-ruled Palestine. This book analyzes the secular, national and anti-colonial ideology of the Hebrew Law of Peace and shows that Jewish religious groups, secular lawyers and leading Zionist institutions undermined the Hebrew Law project. The book develops the concept of 'dual colonialism' to analyze the complex relations between Jewish settlers and British colonizers, and explores the reluctance of leading Zionists to allow a process of nation-building from below that would have allowed communities, rather than organized quasi-state institutions, to define the trajectory of Jewish nationalism.